Modificação superficial de óxidos : proposta de um modelo simples e sua aplicação em sistema aluminazircônia - Dalmaschio, Cleocir José (2008)
In this study a model that makes possible to foresee the limit of modifier oxide of surface that results in the complete support coating with a unit cells monolayer was proposed. From such limit, the lattice of the modifying material should be formed. According to the proposal, the identification of the crystalline phase of the modifier for coating levels lower than the delimited can be an indication that the deposition method adopted does not result in high dispersion. The model s applicability was demonstrated in aluminas coating with zirconium oxide by using a resin obtained through the polymeric precursors method for dispersion of modifier. The characterization results for X-ray diffraction (DRX) presented excellent correlation with the diagram built from the model. Concentrations maps obtained by energy dispersive x-ray spectroscopy (EDS) evidenced that the modifier deposition occurs on the support. Through high resolution transmission electron microscopy (HRTEM) analysis a monophase material (alumina) without indication of amorphous phase was observed below the saturation limit. Above the limit, two different lattice parameters were observed in the images, being one associated to the alumina and other to the tetragonal zirconium oxide. X-ray photoelectron spectroscopy (XPS) analyses proved that the increase in the zirconium oxide concentration is accompanied by enrichment of the surface by the modifier due to the coating formation. With this technique a strong support-coating interaction, with formation of Al-O-Zr bonds, was also detected. X-ray absorption spectroscopy (XAS) analyses reinforced the argument that the lattice was formed for concentrations above the saturation limit proposed in the model. A better dispersion was evidenced using multiple steps for dispersion of the modifier. Zeta potential measurements indicated attractive interactions more intense between support and resin than between modifier and resin, which explain the better dispersion possible when multiple steps were used.